Avaliação do efeito de rutina e curcumina em marcadores oxidativos, hematológicos e purinergicos em ratos com hiperlipidemia induzida - Manzoni, Alessandra Guedes (2022)
The accumulation of lipids, such as total cholesterol, triglycerides, and LDL, in the bloodstream is known as hyperlipidemia. This condition is characterized by generating inflammatory and oxidative damage both in blood vessels and in various organs of the body, which can lead to the development of atherosclerosis. E-NTPDase, 5' nucleotidase and ADA are enzymes of the purynergic system that have the ability to modulate the immune and inflammatory response as well as lipid metabolism. Rutin and curcumin are polyphenols, known to have antioxidant and anti-inflammatory actions and may also be able to modulate the purinergic system. The aim of the present study was to evaluate the hematological, biochemical, oxidative and cellular changes caused by hyperlipidemia, as well as to assess whether the compounds rutin and curcumin are able to prevent these changes. Adult male Wistar rats were pre-treated by gavage with rutin and/or curcumin (50mg/kg) for 30 days. Hyperlipidemia was acutely induced by intraperitoneal administration of Poloxamer-407 (P-407). After 36 hours, the animals were euthanized and blood was collected for hemogram and cell separation, and tissues such as heart, spleen, kidney and liver were collected for the evaluation of the activity of oxidant and antioxidant enzymes, and activity of NTPDase, 5' nucleotidase and ADA. The induction of hyperlipidemia with P-407 caused hematological changes such as a reduction in the number of lymphocytes and eosinophils in relation to total leukocytes, increased levels of uric acid and albumin, as well as increased levels of TBARS and carbonyl in liver, kidney and heart, and caused the reduction of antioxidant defenses in liver and kidney. Changes in the activities of purinergic enzymes in heart membrane and platelets were also observed. Pre-treatments with rutin and/or curcumin were able to reduce the levels of TBARS and carbonyl and increase the antioxidant defenses in the liver and kidney, in addition to preventing changes in hematological parameters. Thus, curcumin and rutin were shown to prevent most of the damage caused by hyperlipidemia.